2014
DOI: 10.1002/acp.3065
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of Intelligence‐gathering Interrogation Techniques from the United States Army Field Manual

Abstract: Despite growing interest in intelligence interviewing, there is little empirical research directly addressing interrogations conducted with the goal of collecting human intelligence (HUMINT). The current study used an experimental intelligencegathering paradigm to test the efficacy of two clusters of emotion-based interrogation approaches from the US Army Field Manual. Results suggest that both Positive and Negative Emotional Approaches increased the collection of information from both guilty and innocent part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 26 publications
3
30
1
Order By: Relevance
“…According to the cited research, the use of emotional approaches leads to an increase in raw data obtained from human sources, the samples used for this purpose summing up both innocent and "guilty" participants. [18] It is also noteworthy that US researchers have focused primarily on the judicial or criminological approach and less on the specific framework of HUMINT activities from the point of view of intelligence organizations, and the approach of the two domains, albeit etymologically similar, carries adaptive mutations both in the conceptual sphere and in the action domain: if the HUMINT approach from a criminological perspective only addresses the use of questions aimed at accepting guilt or innocence, from the point of view of intelligence organizations it is necessary to obtain raw data and useful information in order to clarify some aspects related to national security. The difference between the techniques and methods used in the HUMINT applied in the military and intelligence area, and in the judicial / forensic area is notable and has been explicitly dealt with by researchers Randy Borum and Jacqueline R. Evans which state that this is mainly due to policies that guide the work of the two areas.…”
Section: Benchmarking Of Information Collection Techniques Used In Humentioning
confidence: 99%
See 1 more Smart Citation
“…According to the cited research, the use of emotional approaches leads to an increase in raw data obtained from human sources, the samples used for this purpose summing up both innocent and "guilty" participants. [18] It is also noteworthy that US researchers have focused primarily on the judicial or criminological approach and less on the specific framework of HUMINT activities from the point of view of intelligence organizations, and the approach of the two domains, albeit etymologically similar, carries adaptive mutations both in the conceptual sphere and in the action domain: if the HUMINT approach from a criminological perspective only addresses the use of questions aimed at accepting guilt or innocence, from the point of view of intelligence organizations it is necessary to obtain raw data and useful information in order to clarify some aspects related to national security. The difference between the techniques and methods used in the HUMINT applied in the military and intelligence area, and in the judicial / forensic area is notable and has been explicitly dealt with by researchers Randy Borum and Jacqueline R. Evans which state that this is mainly due to policies that guide the work of the two areas.…”
Section: Benchmarking Of Information Collection Techniques Used In Humentioning
confidence: 99%
“…The difference between the techniques and methods used in the HUMINT applied in the military and intelligence area, and in the judicial / forensic area is notable and has been explicitly dealt with by researchers Randy Borum and Jacqueline R. Evans which state that this is mainly due to policies that guide the work of the two areas. [16] [18] With regard to HUMINT related research in the intelligence area, the american school has focused on using the direct approach and getting a positive emotional valence, to the detriment of a negative one, the purpose of which is to reduce the anxiety and pressure that are the determinants of obtaining false data and information. [21] Regarding the ways to optimize the direct approach technique both Field manual 2-22.3 / 2006 and self-study by other researchers, they can be optimized by adopting a positive approach based on interrelation and rapport creation, but also using fear down techniques (which involves alleviating the source's fears, minimizing them and setting up a climate based on calm and cooperation) and Pride-and-Ego-Up (aimed at raising -in the case of human sources -self-esteem and respect for one's own).…”
Section: Benchmarking Of Information Collection Techniques Used In Humentioning
confidence: 99%
“…Different experimental paradigms in social psychology using students or volunteers have shown that an information-gathering approach yields more relevant information than an accusatorial approach and leads to more diagnostic impressions by third party observers (see for instance Evans et al, 2013). Positive (praise) and negative (deprecation) emotional approaches to interrogation are more efficient than a direct, accusatorial approach (Evans et al, 2014). Also, a series of complex observational studies using a dynamic-interactive approach and content analysis of videorecorded interactions has shown that suspect cooperation was positively influenced by rapport and relationship building techniques, though it was negatively impacted by direct presentation of alleged evidence and confrontation/competition.…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%
“…Traditionally, forensic deception research focuses on police–suspect interviews (Evans et al, in press; Vrij & Granhag, ; Vrij, Granhag, & Porter, ). Although interest remains in this area, researchers increasingly examine information elicitation and deception detection in intelligence interviews.…”
mentioning
confidence: 99%